THE PERSPECTIVE OF THE CLIENTS ON INSURANCE IN ISLAMIC LAW - Nurmala, Leni Dwi (CV. Era Digital Nusantara, 2023)
Humans as social beings in carrying out their lives need to interact with other humans. Human relations in meeting their needs require rules as laws governing procedures for meeting their physical and spiritual needs or in Islamic law it is called muamalah. The method in this writing is Normative Juridical. A juridical approach based on existing laws or regulations. Both Indonesian positive law and Islamic law. As a result, every muamalah activity is basically permissible and not prohibited. But in practice the clarity of the contract is important and becomes a very principle thing because it will determine whether the muamalah is legal or not according to syar'i. In Islamic law insurance is lawful, but there are also opinions that forbid insurance because there are elements of obscurity, elements of gambling, usury, coercion, and some things that are contrary to sharia principles. In conventional insurance there is an agreement based on an uncertain or uncertain event which contains an element of chance as in gambling. The problem of insurance as a reciprocal contract (muawwadhah) which is an exchange (As-Sharf) which is suspended and causes usury nasi'ah because the agreement is a reciprocal agreement in which one of the payments (claims) is deferred and will only be paid if it occurs. a certain event.